2020
DOI: 10.1371/journal.pbio.3000928
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal neurons with stable excitatory connectivity become part of neuronal representations

Abstract: Experiences are represented in the brain by patterns of neuronal activity. Ensembles of neurons representing experience undergo activity-dependent plasticity and are important for learning and recall. They are thus considered cellular engrams of memory. Yet, the cellular events that bias neurons to become part of a neuronal representation are largely unknown. In rodents, turnover of structural connectivity has been proposed to underlie the turnover of neuronal representations and also to be a cellular mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 66 publications
1
30
1
Order By: Relevance
“…Structural synaptic turnover through continuous spine degradation and formation could facilitate future learning by maximizing sampling across this synaptic connectivity space ( Frank et al, 2018 ; Holtmaat and Svoboda, 2009 ; Kappel et al, 2015 ; Minerbi et al, 2009 ; Rumpel and Triesch, 2016 ; Xu et al, 2009 ), increasing the likelihood of achieving certain spiking patterns, and ultimately potentiating their corresponding synaptic weights. Consistent with this logic, spine turnover is critical for birdsong acquisition, fear conditioning, and spatial navigation in zebra finches and mice ( Castello-Waldow et al, 2020 ; Frank et al, 2018 ; Roberts et al, 2010 ). Frank et al, 2018 measured spine turnover in the mouse retrosplenial cortex and found that turnover rates, even before fear conditioning and spatial exploration, positively correlated with individual ability to learn each memory.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Structural synaptic turnover through continuous spine degradation and formation could facilitate future learning by maximizing sampling across this synaptic connectivity space ( Frank et al, 2018 ; Holtmaat and Svoboda, 2009 ; Kappel et al, 2015 ; Minerbi et al, 2009 ; Rumpel and Triesch, 2016 ; Xu et al, 2009 ), increasing the likelihood of achieving certain spiking patterns, and ultimately potentiating their corresponding synaptic weights. Consistent with this logic, spine turnover is critical for birdsong acquisition, fear conditioning, and spatial navigation in zebra finches and mice ( Castello-Waldow et al, 2020 ; Frank et al, 2018 ; Roberts et al, 2010 ). Frank et al, 2018 measured spine turnover in the mouse retrosplenial cortex and found that turnover rates, even before fear conditioning and spatial exploration, positively correlated with individual ability to learn each memory.…”
Section: Introductionmentioning
confidence: 73%
“… Frank et al, 2018 measured spine turnover in the mouse retrosplenial cortex and found that turnover rates, even before fear conditioning and spatial exploration, positively correlated with individual ability to learn each memory. In other words, high spine turnover rates provided a greater number of new spines available for memory encoding but may have also enabled faster sampling across synaptic space and therefore a quicker arrival to a synaptic connectivity pattern that adequately encoded the new information ( Castello-Waldow et al, 2020 ; Frank et al, 2018 ; Rumpel and Triesch, 2016 ; Xu et al, 2009 ). Changes in synaptic connectivity could also heterogeneously influence the likelihood of spiking (intrinsic excitability) in neuronal subpopulations, which would in turn increase their likelihood of participating in future memory-encoding ensembles (i.e., memory allocation; Box 2 ; Buzsáki, 2010 ; Chen et al, 2020 ; Rogerson et al, 2014 ; Yiu et al, 2014 ; Zhou et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this cellular signature is altered in early aging, primarily through a downregulation of the memory encoding-activated cellular network. This paradigm opens the door for future investigation of the molecular mechanisms ( Castello-Waldow et al, 2020 ; Cizeron et al, 2020 ) in incorporation of neurons into a memory trace to enable memory persistence and in improving cognitive aging.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with others showing that ensemble maintenance is heterogenous 81 and not random, favoring the neurons that have high functional importance and pruning those that have lesser significance. For example, Arc-expressing neurons show more synaptic stability and are more integrated in memory ensemble networks 53 . Neurons that have high selectivity for specific spatial trajectories are also selectively stabilized during navigational memory tasks 82,83 .…”
Section: Discussionmentioning
confidence: 99%
“…If the internal co-activity of remodeling ensembles decreases during memory-updating, which neurons were most likely to be the ones that "dropped"? Previous studies have shown that memories are preferentially stored in neurons that are well-connected with their peers [50][51][52][53][54] . Thus, to update the memory during Reversal, we reasoned that the neurons that dropped from the ensemble may be ones that were relatively weakly co-active with the rest of the ensemble to begin with, but the ones that remained were consistently strongly co-active.…”
Section: Ensembles Remodel Due To Decoupling Of Weakly-connected Neuronsmentioning
confidence: 99%